Predicting Leg-Length Change after Total Hip Arthroplasty by Measuring Preoperative Hip Flexion under General Anaesthesia - Takaaki Fujishiro (Journal of Orthopaedic Surgery, 2012)
Purpose. To measure preoperative hip flexion under general anaesthesia in patients with developmental dysplasia of the hip and analyse its correlation with leg-length change. Methods. 79 women and 6 men aged 27 to 82 (mean, 59) years underwent 92 total hip arthroplasties for severe developmental dysplasia of the hip of Crowe types II (n=60), III (n=17), and IV (n=15). All such patients had severe pain and/or considerable difficulty in walking and performing daily activities. 16 of the hips were treated with transverse subtrochanteric shortening osteotomy, whereas the remaining 76 had no femoral osteotomy. Preoperative passive hip flexion was measured under general anaesthesia with a goniometer by a single investigator. Its mean value in patients with Crowe type-III deformity was 60.3°. Therefore, >60° of flexion was defined as high. Postoperative leg-length change was measured radiographically. The distraction of the greater trochanter was equal to the leg-length change in patients treated without femoral osteotomy, whereas leg-length change was calculated by subtracting the amount of resection of the femur from the distraction of the greater trochanter in patients treated with femoral osteotomy. Results. Of the 16 hips treated with a transverse subtrochanteric shortening femoral osteotomy, 2, 2, and 12 were Crowe types II, III, and IV, respectively. In these 16 hips, hip flexion was high in 10 (mean, 86°) and low in 6 (mean, 36°). Leg-length change was significantly greater in the high than low flexion groups (31 vs. 13 mm, p<0.01). In the 76 hips without osteotomy, hip flexion was high in 54 (mean, 85°) and low in 22 (mean, 40°). Leg-length change was significantly greater in the high than low flexion groups (25 vs. 19 mm, p=0.016). Preoperative hip flexion under general anaesthesia correlated with leg-length change in hips with osteotomy ( r =0.850, p=0.0002) and without osteotomy ( r =0.267, p=0.019). Conclusion. Preoperative hip flexion measured under general anaesthesia may predict leg-length change after THA.